2012
DOI: 10.1111/j.1467-9221.2012.00917.x
|View full text |Cite
|
Sign up to set email alerts
|

Should Candidates Smile to Win Elections? An Application of Automated Face Recognition Technology

Abstract: Previous studies examining whether the faces of candidates affect election outcomes commonly measure study participants' subjective judgment of various characteristics of candidates, which participants infer based solely on the photographic images of candidates. We, instead, develop a smile index of such images objectively with automated face‐recognition technology. The advantage of applying this new technology is that the automated process of measuring facial traits is by design independent of voters' subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 13 publications
1
30
0
Order By: Relevance
“…Because Downloaded by [Nanyang Technological University] at 06:00 10 October 2015 politicians have greater control in Twitter than in the mass media over which pictures are presented to voters, they can post more favorable images (such as using friendly, smiling pictures as their icons), which will increase their likability (Horiuchi, Komatsu, & Nakaya, 2012). This leads us to the following hypothesis.…”
Section: Personality Traitsmentioning
confidence: 99%
“…Because Downloaded by [Nanyang Technological University] at 06:00 10 October 2015 politicians have greater control in Twitter than in the mass media over which pictures are presented to voters, they can post more favorable images (such as using friendly, smiling pictures as their icons), which will increase their likability (Horiuchi, Komatsu, & Nakaya, 2012). This leads us to the following hypothesis.…”
Section: Personality Traitsmentioning
confidence: 99%
“…While this may be true, because most of these studies focus on American samples, it remains unknown whether the emotional expressions in official photos also reflect cultural ideals. One exception is Horiuchi, Komatsu, & Nakaya (2012), which compared the official photos of Japanese and Australian lower house legislators using a face recognition program, and found that Japanese smiled less intensely than did Australian politicians. The authors hypothesized that these differences might reflect different cultural values placed on smiling, but they did not empirically test this hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, smiling in a college yearbook was positively related with being married and negatively related with negative emotionality in adulthood (Harker & Keltner, 2001). Horiuchi, Komatsu, and Nakaya (2012) found on the sample of Australian and Japanese pictures of election candidates that in both countries, candidates who smiled had a significantly higher vote share than candidates who did not smile. One of the suggested explanations for this finding is according to the authors a possibility that voters associated smiling with political competence.…”
Section: Smile and Intelligence And Competencementioning
confidence: 94%